Stories of survival: exploring long-term psychosocial well-being in childhood survivors of acute life threatening critical illness: a multiple-case study - Manning, Joseph (2015)
Background: Childhood critical illness is characterised by a rapid and potentially catastrophic loss of physiological reserve caused by a wide variety of illnesses and injuries. In the Western world, death from childhood critical illness is rare due to advances in paediatric intensive care (PIC) provision, medicine, technology and public health. However, surviving PIC can expose children and their families to a complex array of physical, psychological and social problems. Physical disability, chronic illness, delirium, and stress symptoms have been reported to manifest in the immediate to short-term (<six months post-PIC). Existing research has focused on quantifying the outcomes and impact of surviving childhood critical illness. Furthermore, decontextualised, pathologised, and uni-dimensional platforms to inquiry are the dominant approaches used. Collectively, this has impeded understanding of how childhood survivors construct and experience long-term (≥ six months post-PIC) psychosocial well-being.